Nurses' Quality of Life Scale: Validation and Psychometric Properties. Issue 3 (September 2022) - Sili, Alessandro; Maria, Maddalena De; Fiorini, Jacopo; Zaghini, Francesco; Barbarnelli, Claudio
The Nursing Quality of Life Scale (NQOLS) is a 28-item self-report measure evaluating the four dimensions of nurses' quality of life, namely, the physical, emotional, working, and social dimensions. The purpose of this study is to assess the psychometric properties, including validity and reliability, of the NQOLS. The study enrolled 1105 nurses who provided direct assistance to patients. The NQOLS factorial structure was tested using a cross-validation approach via Exploratory Structural Equational Modeling, which confirmed the instrument's four-dimension structure. Reliability was assessed using omega coefficients, proving excellent for all factors. Cluster analysis identified five distinct groups, each composed of participants sharing a substantial similarity with respect to their profile in the NQOLS. These five identifiable clusters presented significant differences not only in the NQOLS but also in the risk of work-related stress, emotional labor, and burnout. The results show that NQOLS is a simple, reliable, lean tool for measuring nurses' overall QoL, whose various parts can additionally be used to answer specific research questions.